Comparative Study Between Metronidazole, Amoxycilin, Omeprazole Based Therapy and Levofloxacin, Amoxycilin, Omeprazole Based Therapy for Helicobactor Pylori Eradication in Peptic Ulcer Disease - Ahmed, Ershad Uddin; Alam, Razibul; Alam, Fakhrul; Ghosh, Chanchal Kumar; Dey, Subash Kanti; Masud, Hasan; Ahmed, Dewan Saifuddin; Bhuiyan, MMR; Miah, Abdur Rahim; Roy, Projesh Kumar; Raihan, ASMA (Journal of Chittagong Medical College Teachers' Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5623 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):29-32